2021
DOI: 10.1162/opmi_a_00044
|View full text |Cite
|
Sign up to set email alerts
|

To Believe Is Not to Think: A Cross-Cultural Finding

Abstract: Are religious beliefs psychologically different from matter-of-fact beliefs? Many scholars say no: that religious people, in a matter-of-fact way, simply think their deities exist. Others say yes: that religious beliefs are more compartmentalized, less certain, and less responsive to evidence. Little research to date has explored whether lay people themselves recognize such a difference. We addressed this question in a series of sentence completion tasks, conducted in five settings that differed both in religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Consistent with the idea that people intuitively differentiate scientific and religious belief, Heiphetz, Landers, and Van Leeuwen ( 2018 ) found that English‐speaking adults in the United States tend to use the word “think” in discussing scientific claims (e.g., “I think the universe started with the Big Bang”) and the word “believe” in discussing religious claims (e.g., “I believe God created the world in seven days”). Evidence for a similar distinction has been documented across several other languages and cultures (Van Leeuwen, Weisman, & Luhrmann, 2021 ).…”
supporting
confidence: 65%
“…Consistent with the idea that people intuitively differentiate scientific and religious belief, Heiphetz, Landers, and Van Leeuwen ( 2018 ) found that English‐speaking adults in the United States tend to use the word “think” in discussing scientific claims (e.g., “I think the universe started with the Big Bang”) and the word “believe” in discussing religious claims (e.g., “I believe God created the world in seven days”). Evidence for a similar distinction has been documented across several other languages and cultures (Van Leeuwen, Weisman, & Luhrmann, 2021 ).…”
supporting
confidence: 65%
“…For example, anthropologists recorded conspiracists saying: "It's not true but I believe it" (Parmigiani, 2021), similar to how indigenous people with witchcraft traditions would say: "I don't believe in witchcraft, but it exists" (Stroeken, 2004). Anthropologists and philosophers have noted that 'believing in' is a very Western concept that does not (always) capture the phenomenology of intuitive epistemological stances (Luhrmann, 2018;Van Leeuwen, 2014;Van Leeuwen et al, 2021). Insight experiences may help explain the ambiguity in these intuitive stances, because, as we saw, insights are part emotional-existential (discovered structure that renews agency in the world) and part epistemic (a sensitivity to evidence, albeit always evaluated on a local, model-dependent level of the individual).…”
Section: Many Flavors Of Conspiracistsmentioning
confidence: 99%
“…Interestingly, a similar tendency to lexically distinguish religious and nonreligious attitudes also occurs in several other languages besides English. Following up on the work of Heiphetz et al (2021), Van Leeuwen, Weisman, and Luhrmann (2022) first asked speakers of English, Fante, Thai, Mandarin, and Bislama to report either a religious claim or a "matter-of-fact" claim using one of two words (which roughly corresponded to think and believe). They then followed up with a free-response version of the same task and vignette-completion completion task.…”
Section: "Thinking" and "Believing"mentioning
confidence: 99%